FRI0010 Metabolic dysregulation accelerates joint degeneration upon mechanically induced cartilage damage, driven by local inflammation; an in vivo rat study. (15th June 2017) - Visser, HD; Mastbergen, S; Kozijn, A; Coeleveld, K; Rijen, MV; Weinans, H; Lafeber, F
Abstract : Background: Obesity is a well-known and important risk factor for osteoarthritis (OA). Moreover, obesity is highly associated with the metabolic syndrome (MetS) 1 . Growing evidence indicates that both OA and MetS are low-grade inflammatory conditions with elevation in systemic inflammatory markers. Nonetheless, it is unclear whether MetS low-grade inflammation induces OA, or contributes to the disease. Objectives: To determine the contribution of metabolic alterations, induced by a High-Fat Diet (HFD), on the onset or progression of OA in a rat model of local cartilage damage. Methods: Forty Wistar rats (12 weeks old, male), were randomly divided over two groups: twenty rats were fed a HFD (60% of the kcal contained fat:D12492i, Research Diets Inc.) while the other animals received a standard diet. After 12 weeks, local articular cartilage damage was induced on the femoral condyles, in one knee joint according to the groove model in 14 rats of each diet group. Remaining animals served as a control group in each arm. At week 24, serum was collected, subchondral bone was assessed by μCT scan (Quantum FX, PerkinElmar, USA), OA severity was evaluated by rat OARSI histopathology score and macrophage presence with CD68 immunostaining from histological sections was assessed. Results: HFD feeding resulted in metabolic dysregulation as indicated by significantly increased metabolic parameters (weight, fasting insulin and total cholesterol) compared to the standard fed rats. HFD feeding alone resulted in mild cartilage degeneration (2±1.1 vs 0.58 ±0.7; p=0.06) and synovial membrane inflammation (1.0±0.6 vs 0.3±0.5; p=0.075) both subscores of the rat OARSI histopathology score. However, when HFD feeding is combined with the surgical model of applied local cartilage damage, OA severity is statistically significant increased compared to the local cartilage damage group on a standard diet (6.2±2.1 vs 3.4±1.4; p=0.001). Synovial membrane inflammation (1.3±0.9vs 0.5±0.5; p=0.011) and multiple large osteophyte formation, demonstrated by histology (0.9±1 vs 0.2±0.4; p=0.04) and quantified on μCT (328±349 μm 3 vs 7±14 μm 3 ; p=0.0001), contributes most to this increased OA severity. Immunohistochemical CD68 expression as observed on both the synovial membrane as well as in the subchondral bone and around the formed osteophytes can explain the increase in selected inflammatory parameters when groove surgery is combined with a HFD (Figure 1 ). Conclusions: This study shows that a HFD induces metabolic alterations and increases the inflammatory state of the joint. This by itself does not result in severe OA. However, when adding a HFD to a mild cartilage damage model of OA, joint degeneration is significantly increased. This progression of joint degeneration appears to be driven mainly by inflammatory responses as demonstrated by an increased CD68 expression in both the subchondral bone and synovium membrane with increased osteophytosis. Hence, our findings indicate that systemic metabolic and subsequent inflammatory factors need an additional trigger to contribute to the progression of the OA. References: Zhuo Q, Yang W, Chen J and Wang Y, Metabolic syndrome meets osteoarthritis. Nat Rev Rheumatol, 2012. 8(12): p. 729–37. Disclosure of Interest: None declared